2021
DOI: 10.3390/ma14010215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curing Conditions on the MECHANICAL and Microstructural Properties of Ultra-High-Performance Concrete (UHPC) Incorporating Iron Tailing Powder

Abstract: It has been reported that iron tailing powder (ITP) has the potential to partially replace cement to prepare ultra-high-performance concrete (UHPC). However, the reactivity of ITP particles in concrete largely depends on the curing method. This study investigates the effects of curing conditions on the mechanical and microstructural properties of UHPC containing ITP. To achieve this objective, three research tasks are conducted, including (1) preparing seven concrete formulations by introducing ITP; (2) charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It is technically feasible to use iron tailings powder as concrete mineral admixture [18,19]. Lu et al [20] found that adding iron tailings powder to cement can improve the compressive strength of concrete. Song Shaomin et al [21] discovered that adding an appropriate amount of iron tailings powder can improve the chloride ion permeability and carbonation resistance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…It is technically feasible to use iron tailings powder as concrete mineral admixture [18,19]. Lu et al [20] found that adding iron tailings powder to cement can improve the compressive strength of concrete. Song Shaomin et al [21] discovered that adding an appropriate amount of iron tailings powder can improve the chloride ion permeability and carbonation resistance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al (2019) and Liu et al (2019) found that the strength of metal tailings powder concrete increases with the increase of fineness. Lu et al (2021) considered that the curing method has a great impact on the iron tailings micro powder concrete. Song et al (2017), Song et al (2019), and Song and Chen (2020) found that tailings powder can replace fly ash to prepare concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, studied the effects of dolomite powder and iron tailing powder on the resistivity, strength and microstructure of cement paste and concrete, and found that the strength of concrete increased and then decreased with the increase in iron tailing powder admixture [ 15 ]. Lu et al, investigated the effect of curing conditions on the mechanical and microstructural properties of ultra-high-performance concrete incorporating iron tailing powder and found that the strength of concrete first increased and then decreased with the increase in iron tailing powder dosing [ 16 ]. Ling et al, conducted an environmental design study of ultra-high performance concrete using iron ore tailings as cement material and found that iron tailings promote optimization of long-term compressive strength and pore structure of concrete [ 17 ].…”
Section: Introductionmentioning
confidence: 99%